Design and synthesis of nanoporous carbon materials using Cd-based homochiral metal–organic frameworks as precursors for supercapacitor application. Issue 31 (20th July 2018) - Zhang, Guangju; Xiu, Siqi; Wei, Ying; Zhang, Qingguo; Cai, Kedi
Abstract : Design and synthesis of nanoporous carbon materials using Cd-based homochiral metal–organic frameworks as precursors for supercapacitor application. Abstract : Two three-dimensional (3D) homochiral metal–organic frameworks [Cd2 (l -tart)2 ] (L-1 ) and [Cd2 (d -tart)2 ] (D-1 ) were constructed and, for the first time, were used as precursors for the design and synthesis of nanoporous carbon materials by the thermal decomposition route. The obtained nanoporous carbon materials exhibited a remarkably enhanced supercapacitance performance, such as large specific capacitance, high rate capability and good cycling stability.